The causes, course and outcomes of World War Two - Plowright, John 1956- (Histories and controversies, 2007)
Plowright presents the war as two distinct but overlapping conflicts (one European, the other Far Eastern), considering neither as merely a prelude to the Cold War, but critically examining their general impact and their relationship with that phenomenon. This timely textbook represents an approachable synthesis of the literature on the subject